„Że zaś w wieku cyfr cyframi tylko poprzeć można twierdzenie...” – raz jeszcze o kondycji polskich badań nad historią gospodarczą - Guzowski, Piotr; Poniat, Radosław (Roczniki Dziejów Społecznych i Gospodarczych, 2015)
“That in the age of numbers, numbers only can be turned to for supporting one’s propositions” – once more on the Polish studies of economic history (Summary) The authors, in referring to the paper written by Rafał Matera and published in this issue, argue that good studies from the field of economic history should 1) offer analyses informed by a social and economic theory; 2) make use of comparative methods, including as an advisable option the quantification of a series of data; 3) create or rely on specialized databases. Through the analysis of a number of works, the authors show that present-day Polish economic historians often fail to meet the requirements outlined above, thus making Polish historiography lag increasingly behind the historiography of other countries.